MUSIK ISLAMI SEBAGAI TERAPI KETENANGAN JIWA PERSPEKTIF AL-FARABI - Farid, Farid Abdul Ghofur; Fauzi, Ahmad (AflahConsilia : Jurnal Bimbingan dan Konseling, 2023)
This research uses library research techniques, with an emphasis on collecting information from the book "al-Musiq al-Kabir" by Al-Farabi and constructing it from various sources, for example books, journals and research that has been carried out. . Abu Nasr Muhammad ibn Muhammad Farabi (Al-Farabi) is known as the "second teacher" after Aristotle because he is seen as one of the pioneers of thinking in the Islamic world. Al-Farabi can also be called a music historian because most of his works are about beautiful sounds. One of his works that examines music as medicine is the book "al-Musiqa al-Kabir". According to Al-Farabi, music can also be used as a means of psychosomatic healing treatment which has an impact on a person's mental peace, because when music is used as a healing medium it can improve, restore and maintain a person's physical, mental, emotional, social and spiritual well-being. Music therapy with Islamic nuances is very effective in relieving tension and stress, strengthening the sensation of relaxation, reducing depression, and overcoming sleep disorders.